Drilling study of bit in gravel environment based on DEM–MBD. Issue 4 (3rd November 2021) - Gao, Kuidong; Liu, Jihai; Wu, Tianjiao; Zeng, Qingliang; Sun, Liqing; Zhang, Xiaodi
Abstract: In the process of rock bolt support for the roadway with floor heave, the rock bolt cannot reach the bottom of the borehole smoothly due to the influence of the collapse gravels around the borehole. In order to solve the problem of difficult rock bolt installation, the auxiliary installation device of rock bolt drilling was innovatively designed. At the same time, a new method of auxiliary bolt installation was put forward, in which a bit was installed at the bottom of the bolt to assist the bolt drilling. The drilling process of the bit was simulated by the co‐simulation of discrete element method (DEM) and multibody dynamics method (MBD). The axial resistance of the bit and the change law of the particles movement were studied under different motion parameters and structural parameters. It was found that the drilling performance of bit was directly related to the motion parameters and structure of bit. And the selection of gravel parameters in DEM was verified by experiments. The research results can provide technical guidance for bit structure design and the selection of motion parameters of bolt drilling auxiliary installation device, and can effectively improve the rock bolt installation efficiency. Abstract : A bit was installed at the bottom of the rock bolt to assist the rock bolt drilling. The drilling process of the bit was simulated by the co‐simulation of discrete element method and multibody dynamics method. The axial resistance of the bit and the change law of the particles movement were studied under different motion parameters and structural parameters.